KONSEP BELAJAR MENURUT PANDANGAN IMAM AL-GHAZALI PERSPEKTIF HADIST TARBAWI: The Implementation of Imam Al-Ghazali's Learning Concept at Al-Azhary Islamic College Cianjur: A Perspective of Hadith Tarbawi - Wulandari, Fitri; Husni Hoer, Uus (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
Hadith serves as an interpretation of the Qur'an in Islamic education, providing a conceptual basis for learning methods that are oriented towards moral and spiritual values. This study aims to analyze Imam Al-Ghazali's learning concept in the perspective of hadith Tarbawi and its implementation at the Al-Azhary College of Islam (STAI) Cianjur. This research uses a qualitative approach with a literature study method, collecting and analyzing various literature related to Al-Ghazali's educational concepts and relevant hadith. The results showed that Imam Al-Ghazali developed the concept of learning based on the uswah hasanah of the Prophet Muhammad SAW, with an emphasis on morals, the pursuit of knowledge as worship, and gradual learning according to the intellectual capacity of students. In his curriculum, Al-Ghazali emphasized moral-based education and a spiritual approach to get closer to Allah SWT. The implication of this research shows that Al-Ghazali's concept of education is still relevant to modern learning systems, especially in Islamic educational institutions. The integration of these values can strengthen students' academic and spiritual foundations, producing graduates who are not only knowledgeable but also have a strong moral character.